2000
DOI: 10.1093/jpepsy/25.6.427
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stress in Mothers of Children With Cerebral Palsy in Bangladesh

Abstract: Ensuring practical help for mothers and advice on managing common behavior problems are important components of intervention, as they may directly help to relieve stress on mothers of young disabled children in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
111
4
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 26 publications
18
111
4
7
Order By: Relevance
“…This study has tried to look at the progress of children after a similar intervention programme offered to them during a limited period of time, together with improvements in activities of daily living and enrolment into schools. Results have shown significant differences in a number of social communication skills which are consistent with the results of the previous study 13,14 . In addition, this study has shown significant improvement in activities of daily living such as, toilet training which are time consuming activities for mothers adding to their burden of stress and care for these children as shown in a previous study 14 .…”
Section: Volume 16 Issue 2 July 2017supporting
confidence: 91%
“…This study has tried to look at the progress of children after a similar intervention programme offered to them during a limited period of time, together with improvements in activities of daily living and enrolment into schools. Results have shown significant differences in a number of social communication skills which are consistent with the results of the previous study 13,14 . In addition, this study has shown significant improvement in activities of daily living such as, toilet training which are time consuming activities for mothers adding to their burden of stress and care for these children as shown in a previous study 14 .…”
Section: Volume 16 Issue 2 July 2017supporting
confidence: 91%
“…From the demographic information of the participants there is actually not any significant variation on severity of the feeding difficulties in case of variations of ages. In a population based study children aged 2-9 years in Bangladesh by Mobarak R et al estimated the prevalence of moderate to severe disability with specially feeding problem due to cerebral palsy 10 . In a population based study by Adams MS et al found that 28 children among 37 has been significantly improved after feeding training who have had moderate to severe CP and the investigator did not found any correlation between ages and feeding difficulties 8 .…”
Section: Discussionmentioning
confidence: 99%
“…O estresse materno na PC tem sido explicado por diferentes variáveis que incluem aspectos sociodemográficos, assim como, características da mãe, perfil comportamental da criança (Mobarak et al, 2000) tempo de cuidado e recursos de enfrentamento (coping). A investigação a partir de Mobarak et al, (2000).…”
Section: Discussionunclassified